Natural hazard vulnerability quantification of offshore wind turbine in shallow water. (1st August 2019) - Pokhrel, J.; Seo, J.
Highlights: Structural analysis of an offshore wind turbine subjected to wave loads was done. Wind and wave loads acting on the offshore wind turbine were simulated. Wind and wave hazard vulnerability analysis of the offshore wind turbine was completed. Wind and wave fragility surfaces of the wind turbine were created. A difference in the fragility was found due to the variation in wind and wave characteristics. Abstract: Offshore Wind Turbines (OWTs) are prone to numerous natural hazards related to wind and wave loads, causing different levels of structural damage. This paper aims at simulating such loads acting on an OWT and performing its vulnerability analysis in the form of fragility curves. The OWT used for the analysis is 5-MW National Renewable Energy Laboratory (NREL) baseline model in 20 m water depth. Initially, the analysis considering variability in wave characteristics was done due to computational cost by performing three different approaches: analytical approach using Morison's Equation; Finite Element Analysis (FEA) approach; and Computer Aided Engineering (CAE) tool using Fatigue, Aerodynamics, Structures, and Turbulence (FAST) approach. The results coupled with First Order Reliability Method (FORM) were used to develop wave fragility curves, indicating that the FAST approach resulted in a reasonable conservative range in the fragility curve. The FAST approach was further used to simulate wind-and-wave hazard vulnerability of the OWT. To that end, extreme loading scenarios specified by the International Electro-technical Commission (IEC) Design Standard was utilized. Structural responses of the OWT captured at various locations, resulted in flexural demands at the mudline to be critical, and was used to create the multi-hazard fragility surface. This study found that the exceedance probability increased with an increase in both wind speed and wave height, especially above 12 m/s and 10 m, respectively. Through the comparison of regular and irregular wave fragility data, the significant difference in the exceedance probability was also found.